Evaluating the impacts of the EU-ETS on prices, investments and profits of the Italian electricity market - Francesca Ponenti; Giorgia Oggioni; Elisabetta Allevi; Giacomo Marangoni (Fondazione Eni Enrico Mattei (FEEM), 2011)
In this paper we investigate the economic impacts of the European Emission Trading Scheme (EU-ETS) on the Italian electricity market by a power generation expansion model. In particular, we assume that generators make their capacity expansion decisions in a Cournot or in a perfect competition manner. This model is used to measure the effects of the EU-ETS Directives on electricity prices and demand, investments and generators' profits both in an oligopolistic and in a perfectly competitive organization of the power market. We adopt a technological representation of the energy market which is discretized into six geographical zones (North, Center-North, Center-South, South, Sicily, Sardinia) and five virtual poles (Monfalcone, Foggia, Brindisi, Rossano, Priolo) with limited production for a total of eleven zones. We assume that generators operate in different zones connected by interconnections with limited capacity and produce energy by running existing or new plants in which they directly invest. We consider several investment scenarios under the CO2 regulation with and without incentives to renewables. The scenarios also include simulations on future effects of the third EU-ETS phase on the system. Our analysis shows that perfect competition induces generators to invest more than in an oligopolistic framework, but in both market configurations, investments are mainly concentrated in fossil-red plants (CCGT and coal), leaving a small proportion to new wind plants. This happens also in presence of incentives given to renewable technologies. We can thus conclude that investments in a secure and efficient technology like CCGT are preferable compared to those in renewables that cannot be used with continuity. This investment policy affects electricity prices that significantly increase in 2020 compared to their 2009 levels. The raise of electricity prices in 2020 is particularly favorable for generators operating as Cournot players which are able to increase their profits compared to 2009, despite the full auctioning system foreseen for the allocation of CO2 allowance to the power sector in the third EU-ETS phase. The solution of the overall system is found by exploiting the mixed complementarity theoretical framework and solution algorithms. The developed model is implemented as complementarity problems and solved in GAMS using the PATH solver.
Keywords: Q4; Q48; 330; Complementarity Conditions; General Equilibrium Models; EU-ETS; Italian Electricity Market